'Lex Cryptographi(c)a, ' 'Cloud Crypto Land' or What? – Blockchain Technology on the Legal Hype Cycle. Issue 1 (29th May 2022) - Anderson Schillig, Michael
Abstract : Based on the reception of DLT/blockchain, this article argues that legal discourse is subject to hype cycle dynamics. Thinking in hype cycle categories provides a structured way for analysing the legal implications of a particular innovation. This critical engagement with enthusiasts, sceptics and pragmatists through the different stages may help to present a more realistic picture of DLT/blockchain's potential from a legal perspective in the short and medium term. Consequently, this article discusses the potential for disruption to the legal system envisaged by enthusiasts at the height of inflated expectations, attempts to deconstruct the arguments levelled at the technology by its detractors during the trough of disillusionment, charts the emerging legal landscape that seeks to harness the potential of DLT/blockchain up the slope of enlightenment, and concludes by risking a glimpse towards the plateau of productivity.